2019
DOI: 10.12669/pjms.35.3.81
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Topo IIα and Ki67 in breast cancer and its clinicopathologic features and prognosis

Abstract: Objective: Breast cancer is one of the most common malignant tumors in women, and its incidence in women has ranked the first place among all malignant cancers. The evolution of breast cancer which is highly heterogeneous is a complex biological process involving multiple factors, genes and stages. Therefore, studying the expression and interaction of related genes is of great significance to further revealing of the mechanism of the occurrence and development of breast cancer and reduction of its resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Several studies had already proved that P53 was related to carcinogenesis and poor prognosis in patients with GC [22,23]. It was reported that Topo II and Ki67 could reflect the proliferation activity of cancer cells and affect the postoperative recurrence in breast cancer [24]. However, several studies had proved that Topo II was not associated with LNM [16,25].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had already proved that P53 was related to carcinogenesis and poor prognosis in patients with GC [22,23]. It was reported that Topo II and Ki67 could reflect the proliferation activity of cancer cells and affect the postoperative recurrence in breast cancer [24]. However, several studies had proved that Topo II was not associated with LNM [16,25].…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, the expression levels of Topo‐IIα were found to be closely related to tumor cell proliferation and aggression . The relationship of expression of Topo‐II and Ki‐67 has also been reported in malignant tumors …”
Section: Introductionmentioning
confidence: 89%
“…Numerous studies have observed the association of cell proliferation with the aggressive biological behavior of tumors of different localization [9][10][11][12], while the expression of Ki67 protein has been identified as a good predictor of recurrence and as an independent prognostic factor of survival rate [12,13].…”
Section: Discussionmentioning
confidence: 99%